Designing a Generative STEM Model Based on Subak Landscape: Integrating Entropic Modulation and Indigenous Ecological Knowledge into Science Education - Surata, Sang Putu Kaler; Arjaya, Ida Bagus Ari; Hermawan, I Made Surya; Payadnya, I Putu Ade Andre; Eglash, Ron (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
This study introduces and evaluates a generative STEM education model grounded in the Subak landscape of Bali, designed to integrate Indigenous ecological knowledge with contemporary science learning frameworks. The model draws on the principles of generative justice-defined as value circulation within communities-and entropic modulation-a concept referring to balancing variation and structure for resilience. Culturally Situated Design Tools (CSDTs), which are simulation-based tools for visualizing ecological processes, were employed to model sustainable farming practices in Subak, focusing on intermittent irrigation data that connects water surface levels, drying periods, drying duration, and timing with changes in temperature, methane emissions, and rice yield. A mixed-methods approach was applied, combining design-based research, participatory action research, classroom observations, focus groups, and pre/post assessments. Preliminary findings indicate a 27% improvement in students’ conceptual understanding, particularly regarding Subak water management, greenhouse gas emissions, and the relationships between irrigation practices, environmental conditions, and rice production. These findings demonstrate that the Subak-based generative STEM model not only enhances student engagement, systems thinking, and ecological literacy but also offers concrete evidence for developing a culturally grounded framework for decolonizing STEM education.